Renal function and cardiovascular risk in rheumatoid arthritis - N. A. Khramtsova; A. A. Dzizinsky (Кардиоваскулярная терапия и профилактика)
Aim. To study renal function and its association with cardiovascular risk factors in rheumatoid arthritis (RA). Material and methods. The study included 257 RA patients aged 29—69 years. Results. Reduced glomerular filtration rate (GFR) <60 ml/min was observed in 146 (56,8 %) RA patients. Renal dysfunction was associated with non-steroid anti-inflammatory drug (NSAID) therapy (OR 24,5; p<0,01), microalbuminuria (OR 17,8; p<0,01), high RA activity by DAS 28 (OR 6,1; p<0,01), pulse blood pressure (PBP) >55 mm Hg (OR 4,38; p<0,01), arterial hypertension (AH) (OR 3,15; p<0,01), atherogenic dyslipidemia (DLP) (OR 2,83; p<0,01), RA duration >10 years (OR 2,8; p<0,01), hyperglycaemia (OR 2,35; p<0,05), age >50 years (OR 2,17; p<0,01) and “non-dipper” BP profile (OR 1,85; p<0,05). GFR negatively correlated with vascular stiffness index (r=-0,23; p<0,01), LV myocardial mass index (r=-0,2; p<0,05), C-reactive protein level (r=-0,31; p<0,01), RA activity by DAS 28 (r=-0,29; p<0,01), age (r=-0,33; p<0,01), RA duration (r=-0,29; p<0,01), intima-media thickness (IMT) (r=-0,28; p<0,01), mean circadian systolic BP level (r=-0,19; p<0,05) and PBP level (r=-0,31; p<0,01), as well as SCORE-assessed cardiovascular risk level (r=-0,17; p<0,05). Conclusion. In RA, GFR reduction is a complication of chronic inflammation and long-term NSAID therapy. It is associated with AH, atherogenic DLP, and high cardiovascular risk.